President’s residence energy analysis - Gorney, Elizabeth A. (Kansas State University, 2011)
The conservation of energy is an increasingly important issue. To raise awareness of energy conservation, the State of Kansas initiated the Take Charge Challenge, which focuses on energy conservation in homes across Kansas. The program pits city against city in a competition to determine which city can conserve the most energy in one year. In the spirit of friendly competition, Manhattan, Kansas, home of the Kansas State University Wildcats, and Lawrence, Kansas, home of the University of Kansas Jayhawks, competed in the Challenge during 2011. At the end of the Challenge, Kansas State was victorious saving a total of 5,783 million Btu (MMBTUs). In the Spring of 2011, Noel Shultz, first lady of Kansas State University and co-chair of the Take Charge Challenge in Manhattan, set an example for other area residents by having an energy audit performed on her home, the historic Kansas State University President's Residence. The author used the audit, which was performed by an independent company, thermal images, a lighting survey, and various performance calculations to examine energy use in the building. The audit results include suggested improvements in order of importance. The suggestions were to install programmable thermostats, reduce air infiltration, and increase insulation. These improvements have the potential to provide a return on investment, although not all the suggestions are applicable to the home because of its historic nature. Other improvements, such as replacing lamps and insulating windows, were also researched by the author as means to reduce energy use. This paper compares the audit results and the author's calculations to verify whether the suggestions are feasible and would provide a return on investment. Materials were donated by Kansas State University’s Facilities Department for the improvements. Students and faculty volunteers participated in a work project to install the donated material. Only days after the insulation was installed, Mrs. Shultz mentioned that the family could feel an improvement in comfort. Thermal images of the roof verified that the insulation had reduced the heat loss. It is hoped that the improvements will also reduce energy consumption during the winter months.
Keywords: President's residence; Energy; Architectural engineering (0462)